Hierarchical Honey Bee Model to Avoid Sleep Deprivation Attack in MANET - Madhurikkha, S; Sabitha, R (International Journal of Engineering and Technology, 2018)
Ad-hoc networks are highly vulnerable to the attacks due to the dynamic nature of the network topology, lack of centralized management and cooperative algorithm. Nodes in the ad-hoc network are responsible to transmit packets to other nodes. One of many different kinds of attacks, a node may experience the exhaustion of power by consuming its batter power. Routing protocol controls the packet transmission over the network and calculates the routing path for transmission. The predefined static routed path is limited in ad-hoc network, and nodes have limited energy that is depleted due to transmission. Sleep deprivation attack constantly drops the power source on a particular node until the node gets shutdown. We have proposed an effective model named Honey-bee model to enhance Ad-hoc On-Demand Distance Vector Routing algorithm. Hierarchical clustering method is used for the formation of the cluster of nodes. Based on this approach, each node is assigned with a cluster that prevents the attack. We have simulated in ns2 tool compared results with other on-demand routing protocol such as Power Aware Routing Protocol, Dynamic Source Routing, Flow-State extensions to Dynamic Source Routing and AODV.Â Â